The Persian Revival : The Imperialism of the Copy in Iranian and Parsi Architecture - Grigor, Talinn, 1972- (Book collections on Project MUSE., 2021)
"Examines Europe's discovery of ancient Iran, first in philology and then in art history, and explores the Persian Revival movement in light of imperial strategies of power, selfhood, and statehood in British India and Zand-Qajar-Pahlavi Iran"--